2019
DOI: 10.16984/saufenbilder.513294
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Research of Energy Consumption of Austenitizing Heat-Treated Casting Fittings in Pipe Threading

Abstract: Energy consumption is an important part of the production cost of mass production industrial enterprises. The casting, heat treatment and threading processes involved in the industrial production of fittings result in high energy consumption. In serial production, the threading of pipe fittings is carried out using high torque and low speed. The thin-walled designs of the fittings lead to rapid cooling, causing the formation of a high rate of pearlite microstructures and subsequent low or extremely hard machin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 22 publications
1
5
0
Order By: Relevance
“…e results obtained are similar to those of studies in the literature [11][12][13][14][15]. It was observed that the hardness values increased by 25% on average by rapid cooling of the AA 6063 alloy after extrusion.…”
Section: Tensile Test and Hardness Measurement Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…e results obtained are similar to those of studies in the literature [11][12][13][14][15]. It was observed that the hardness values increased by 25% on average by rapid cooling of the AA 6063 alloy after extrusion.…”
Section: Tensile Test and Hardness Measurement Resultssupporting
confidence: 89%
“…e air-cooled samples have grain sizes of 150-165 μm, whereas the grains of the watercooled ones are 18-25 μm. is was a result of the cooling rate differences because when the cooling rate is slow, it leads to slow nucleation and large grain size [13,14,27]. Consequently, cooling with water can result in a particle size six times smaller than that can be obtained with air cooling.…”
Section: Microstructure and Eds Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In order for statistical analyses to be considered reliable, error values must be below 20% [28,29]. Many important studies have been carried out on energy consumption during the machining process [30][31][32][33]. e comparison of surface roughness and energy consumption values (Table 8) underscores the fact that the level of difference between the results of the confirmation test and those obtained via the Taguchi method was insignificant.…”
Section: Confirmation Testsmentioning
confidence: 99%